The semantics of Afro-Brazilian spirits: Applying Davidson on prior and passing theories - Engler, Steven (Religious studies, 2025)
Based on fieldwork with two related Afro-Brazilian religions, Umbanda and Quimbanda, this article explores the value of Donald Davidson’s semantic theory for making sense of ethnographic fieldwork. Specifically, we look at the role of scriptedness in communication, including religious ritual. We first clarify the role of social externalities in Davidson’s view of communicative interpretation, which is broader than his initial framework of radical interpretation. We then offer an account of what constitutes communicative and interpretational success, by drawing on Davidson’s account of prior and passing theory. Prior theories are interpreters’ initial hypothetical frameworks, ranging from general (e.g., the rational, intentional nature of self and other, and a shared perceivable world) to local (e.g., assumptions about cultural, social, and institutional contexts). Passing theories are tactical, on-the-fly modifications that we hypothesize in order to get mutual understanding back on track. We introduce the concept of ‘semantic reduction’ to operationalize the view that specific, local social externalities provide clues that help keep interpretation on track. In the case of religious ethnography, these include ritual, doctrinal, narrative, symbolic, material, temporal, and spatial frames that constrain the generation of passing theories. Examples from fieldwork illustrate the potential value of our appeal to Davidson’s ideas.